Charlotte’s Language Style in Queen Charlotte: A Bridgerton Story Series (2023) - Nabilah, Hana; Candria, Mytha (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2023)
Queen Charlotte: A Bridgerton Story is one of the popular Netflix series in 2023. This series is famous for being the aftermath of the two Bridgerton series that were released previously. The story, which is set in the British Empire at the end of the 18th century, attracts the attention of audiences. It is prominent to apply into the theory used because the various social factors and dimensions in the series can provide the samples of the five types of language styles according to Joos (1967), from frozen styles to intimate styles. The data used in this study are Charlotte’s utterances to the three main supporting characters. Data collection uses the observation method by analyzing the dialogues in the series. There are 373 data found with the style that appears most often is the casual style. This type of language style is usually used in informal situations, with intimate relationships between participants.